A controllable low-frequency broadband sound absorbing metasurface. (22nd June 2021) - Liang, Qingxuan; Lv, Peiyao; He, Jin; Wu, Yutao; Ma, Fuyin; Chen, Tianning
Abstract: Low-frequency noise control has aroused continuous interests owing to the intolerant structural thickness of traditional sound absorbing materials comparable to the working wavelength. The low-frequency sound absorbing materials remain challenging in scientific and engineering communities until now. Herein, a controllable broadband sound absorbing metasurface is designed and fabricated successfully by combining micro-perforated panel, coiled channel and embedded partition boards with the thickness of only 7 cm. The proposed metasurface possesses an average absorption coefficient over 0.8 within 0°–75° wide incident angle. Most importantly, the frequency of the absorption peak could be tuned flexibly by changing the number of partition boards in the cavity, providing an effective way for sound absorption on-demand design. The proposed acoustic metasurface opens the possibility of real-life application in low-frequency noise control engineering field.